Childhood Trauma and Cortisol Reactivity: An Investigation of the Role of Task Appraisals - Counts, Cory J.; Ginty, Annie T.; Larsen, Jade M.; Kampf, Taylor D.; John-Henderson, Neha A. (Frontiers in Psychology, 2022)
Background Childhood adversity is linked to adverse health in adulthood. One posited mechanistic pathway is through physiological responses to acute stress. Childhood adversity has been previously related to both exaggerated and blunted physiological responses to acute stress, however, less is known about the psychological mechanisms which may contribute to patterns of physiological reactivity linked to childhood adversity. Objective In the current work, we investigated the role of challenge and threat stress appraisals in explaining relationships between childhood adversity and cortisol reactivity in response to an acute stressor. Methods Undergraduate students (n = 81; 61% female) completed an online survey that included general demographic information and the Risky Families Questionnaire 24 h before a scheduled lab visit. In the lab, a research assistant collected a baseline salivary cortisol sample. Following the baseline period, participants were read instructions for the Trier Social Stress Test (TSST), a validated psychological lab stressor. Next, they completed a challenge vs. threat task appraisal questionnaire and completed the speech and math portion of the TSST. Twenty minutes following the start of the TSST, a second salivary sample was collected to measure changes in salivary cortisol following the TSST. Results Linear regression analyses adjusted for age, sex, childhood socioeconomic status (SES), and baseline cortisol levels, showed childhood adversity associated with changes in cortisol levels [B = –0.29 t(73) = –2.35, p = 0.02, R2=0.07]. Linear regression analyses controlling for age, sex, and childhood SES showed childhood adversity associated with both challenge [B = –0.52 t(74) = –5.04, p < 0.001, R2=0.24] and threat [B = 0.55 t(74) = 5.40, p < 0.001, R2=0.27] appraisals. Significant indirect effects of childhood trauma on cortisol reactivity were observed through challenge appraisals [B = –0.01 (95% confidence interval = –0.02, –0.003)], and threat appraisals [B = –0.01 (95% confidence interval = –0.01, –0.003)]. Conclusion Childhood adversity may contribute to blunted cortisol reactivity, a pattern of response which is linked to obesity, addiction, and other behavior-related diseases. Our findings suggest that this relationship is in part a product of stress appraisals.